Community resurgence as an answer to the new socioeconomic reality - Barrera Algarín, Evaristo; Sarasola Sánchez Serrano, José Luís; Malagón Siria, José Carlos (REVESCO. Revista de Estudios Cooperativos, 2017)
This study analyzed the characteristics of community movements which have grown along the economic crisis in recent years. The research was conducted in four specific contexts of community experiences: Two in Social Money, one in Urban Gardens, and the last one in Time’s Banks. Hypothesis: community-based movements involving aid economic aspects of families and individuals are becoming stronger in times of economic crisis, in the economic globalization context. Methodology: 82 surveys trough the ECOM Questionnaire, composed of 48 questions and 77 variables. The study provided us the connection between the crisis and unemployment; linking participant's age with the different contexts; unemployed university in the origin to participation; consideration of these community initiatives as a way of market or as an alternative economy; linkage with the principle of commons; participation based on trust; and the disconnection between the global and the local within these initiatives.
Keywords: Sharing economy; The Commons; Globalization; Territorialization; Global-Local